With Corona Outbreak: Nature Started Hitting the Reset Button Globally - Kumar, Ashwani; Malla, Muneer Ahmad; Dubey, Anamika (Frontiers in Public Health, 2020)
Considering the potential threat and the contagious nature of the Covid-19 pandemic, lockdowns have been implemented worldwide to stop the spread of this novel virus. The coronavirus pandemic has hit the world severely, representing the most severe threat to human health in more than a century. The environment from local to global scales has witnessed apparent positive and negative impacts. Global lockdowns have drastically altered the patterns of energy demand and have caused an economic downturn but at the same time, have provided an upside-cleaner global environment. Such immense unintended advantages offer opportunities for unprecedented insights into the dynamics of our natural and built environments that can lead to viable paths for the conservation and perpetuation of the recovered environments and through sensible policies and practices that can help to create new recovery pathways. Knowledge gained from the studies suggests that a substantial relationship exists between the contingency measures and environmental health. Here in this review, the authors discussed the impact of coronavirus pandemic on human life, healthcare organizations, and the environment. The parallels between the Covid-19 and other diseases are mentioned. Finally, the impact of Covid-19 on society and the global environment has also been highlighted.